2020
DOI: 10.3390/ijms21113924
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Inhibits the Proliferation of Human Bone Marrow-Derived Mesenchymal Stem Cells via β2-Adrenoceptor-Mediated ERK1/2 and PKA Phosphorylation

Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) represent an alternative to chondrocytes to support cartilage regeneration in osteoarthritis (OA). The sympathetic neurotransmitter norepinephrine (NE) has been shown to inhibit their chondrogenic potential; however, their proliferation capacity under NE influence has not been studied yet. Therefore, we used BMSCs obtained from trauma and OA donors and compared the expression of adrenergic receptors (AR). Then, BMSCs from both donor groups were treated with NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…In contrast, b 2 -AR stimulating effects of SH1293 (i.e., terbutaline) have previously been demonstrated to promote chondroclastic activity by inducing RANKL (45,82). At high, but not low concentrations, norepinephrine can inhibit chondrogenesis in BMSCs via ERK1/2 and PKA mediation, effects that are blocked by the b 2 -AR blocker, propranolol (83). Our data indicates that treatment with SH1293 delayed and suppressed articular cartilage resorption in the distal tibia in arthritic rats, findings that support direct inhibitory effects of terbutaline on chondrocyte proliferation.…”
Section: Sh1293 Influence On Subchondral Bone Articular Cartilage and Chondrocytesmentioning
confidence: 97%
“…In contrast, b 2 -AR stimulating effects of SH1293 (i.e., terbutaline) have previously been demonstrated to promote chondroclastic activity by inducing RANKL (45,82). At high, but not low concentrations, norepinephrine can inhibit chondrogenesis in BMSCs via ERK1/2 and PKA mediation, effects that are blocked by the b 2 -AR blocker, propranolol (83). Our data indicates that treatment with SH1293 delayed and suppressed articular cartilage resorption in the distal tibia in arthritic rats, findings that support direct inhibitory effects of terbutaline on chondrocyte proliferation.…”
Section: Sh1293 Influence On Subchondral Bone Articular Cartilage and Chondrocytesmentioning
confidence: 97%
“…Akin to iSCs, MSCs also have multipotent stem cell activity. MSCs reside in multiple organs, including bone marrow, umbilical cord, amnion, and brain [ 90 , 91 , 92 , 93 ]. Although it remains unclear whether brain pericytes are identical to brain MSCs [ 94 ], it was reported that the traits of MSCs differ among organs [ 95 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
“…Furthermore, autocrine and paracrine effects of sASCs can be excluded because TH was neither detected in monolayer nor in chondrogenic sASCs cultures. This is in agreement with previous findings in OA chondrocytes (Speichert et al 2019) or BMSC derived from trauma or OA patients that did not express TH (Jenei-Lanzl et al 2014;Hedderich et al 2020). Since joint resident MSC and chondrocytes express AR, an interaction between these cells with neurotransmitters including NE was proposed, which is also supported by other studies (Takarada et al 2009;Mitchell et al 2011).…”
Section: Ar Expression In Sascssupporting
confidence: 92%
“…This study, demonstrated that the treatment with NE was not toxic in any of the tested concentrations and did not influence cell proliferation, indicating that NE in the knee-joint might not influence the proliferation or viability of sASCs. This is in line with another study showing that NE did not affect the viability of human OA chondrocytes (Speichert et al 2019) Interestingly, the proliferation of both OA and trauma BMSC was inhibited dose-dependently by NE without affecting cell viability (Hedderich et al 2020). Treatment with the highest concentration of 10 −6 M NE reduced the proliferation of OA BMSC significantly through the activity of β2-AR signalling pathway.…”
Section: Proliferation Of Sascs In Presence Of Nesupporting
confidence: 87%
See 1 more Smart Citation